Assessment financial security of the banking system in Ukraine - N.S. Pedchenko; S.M. Diachek (Економіка, управління та адміністрування)
This article is devoted to the studying the methodological approaches to assessing the financial security level of the banking system. It is proposed to supplement the set of indicators defined by the Methodology for assessing the level of economic security in terms of banking security, such as: ratio of total assets of the banking system to GDP, ratio of external debt to total assets of banks, return on assets of the TOP-10 largest banks, profitability of banks which will allow for a more detailed assessment of the financial security level of the banking sector and take the necessary measures to prevent the effects of negative factors. The authors analyze the main indicators of the banking component of the financial security in Ukraine during 2007-2018. Considerable attention is paid to the analysis of the quality of the credit portfolio of the banking system. The main external and internal factors that caused an increase in the share of long-outstanding accounts payable in the credit portfolio of the domestic banking system are identified. Based on the analysis, it is concluded that, both in the crisis and post-crisis periods, the vast majority of indicators exceed the safe limits, which indicates a critically low level of financial security of the Ukrainian banking system.